Fuzzy reinforcement learning and its applications to mobile robot navigation - Deng, Chang (2008)
Fuzzy logic is a mathematical approach to emulate the human way of thinking. It has been shown that fuzzy logic could serve as a powerful methodology for dealing with imprecision and nonlinearity efficiently. However, the conventional way of designing a fuzzy system has been a subjective approach. If the fuzzy system somehow possesses learning abilities, an enormous amount of human efforts would be saved from tuning the system.